Secondary metabolites of Alternaria alternate appraisal of their SARS-CoV-2 inhibitory and anti-inflammatory potentials. - Fatma A Moharram; Reham R Ibrahim; Shahenda Mahgoub; Mohamed S Abdel-Aziz; Ahmed M Said; Hui-Chi Huang; Lo-Yun Chen; Kuei-Hung Lai; Nashwa Hashad; Mohamed S Mady (PLoS ONE)
This study identifies the secondary metabolites from Alternaria alternate and evaluates their ACE-2: Spike RBD (SARS-CoV-2) inhibitory activity confirmed via immunoblotting in human lung microvascular endothelial cells. In addition, their in vitro anti-inflammatory potential was assessed using a cell-based assay in LPS-treated RAW 264.7 macrophage cells. Two novel compounds, altenuline (1), phthalic acid bis (7'/7'' pentyloxy) isohexyl ester (2), along with 1-deoxyrubralactone (3) alternariol-5-O-methyl ether (4) and alternariol (5) were identified. Molecular docking and in vitro studies showed that compounds 2 and 4 were promising to counteract SARS-CoV-2 attachment to human ACE-2. Thus, they are considered promising natural anti-viral agents. SwissADME in silico analysis was conducted to predict the drug-like potential. Immunoblotting analysis confirmed that the tested compounds (1-4) demonstrated downregulation of ACE-2 expression in the endothelial cells from the lungs with variable degrees. Furthermore, the tested compounds (1-4) showed promising anti-inflammatory activities through TNF-α: TNFR2 inhibitory activity and their inhibitory effect on the proinflammatory cytokines (TNF-α and IL-6) in LPS-stimulated monocytes. In conclusion, our study, for the first time, provides beneficial experimental confirmation for the efficiency of the A. alternate secondary metabolites for the treatment of COVID-19 as they hinder SARS-CoV-2 infection and lower inflammatory responses initiated by SARS-CoV-2. A. alternate and its metabolites are considered in developing preventative and therapeutic tactics for COVID-19.